Stakeholder Participatory Design and Development of an Agri-Infotech Portal - Sakeer Hussain, A; Ahamed, P; Nithin, KM (Journal of Agricultural Extension Management, 2018)
The Agri-Infotech Portal (www.celkau.in), developed by Centre for e-learningof Kerala Agricultural University (KAU) is an ICT enabled bi-lingual platformfor demand-driven technology information and advisory services in the agrifront,covering agriculture, animal husbandry, fisheries and allied aspects. Italso acts as a platform for online course management in agriculture. As onAugust 2016, the portal had nearly 16 lakh hits within four years, which showa geometric progression. Besides, the portal won two international awards,one national award and the Kerala Government’s e-governance award. Thispaper analyses the methodology followed for designing and developing thishigh-end utility web portal. To accomplish this, a basic research mode workon user-centred design, testing, refining and launching of the portal wasadopted, as it would match the priorities of its end-users. The utility wasensured by testing and fine-tuning from its designing stage itself. Creating aworking model (prototype) before developing the actual portal was the firststage. To generate content, the information needs of the users were identifiedand prioritized through questionnaires, brainstorming sessions, and focusgroup discussions. Interpretations based on the priorities, suggestions fromthe users, and desktop analyses of various similar portals across the world, ledto designing of the first prototype. This prototype was subjected to a process ofcriteria/trait based evaluation by the end-users for further refinement leadingto the second prototype. This second prototype was demonstrated beforevarious categories of end-users and stake holders for final fine-tuning.